Study of the Stress Distribution due to the Effect of Transient Analysis on a Vertical Pressure Vessel and Validation using the Mesh Independence Study - Faro, Abdulfatai; Salam, Kazeem; Jeremiah, Oludare; Akinwole, Isreal; Bukola, Animashaun (Journal of Advanced Mechanical Engineering Applications, 2021)
The importance of Pressure Vessel (PV) to industries is one of the reasons why the design and structural integrity should be fully understood and considered when deploring it in under different conditions. The design of such vessels need to be broadened with a detailed thermal stress due to its time-dependent different behaviours experienced under load. Therefore, this study aimed at investigation of transient analysis of PV when subjected to different operating condition.  The PV used for this simulation was designed based on American Society of Mechanical Engineers (ASME) Boiler and Pressure Vessel Code (BPVC) 2019 and subjected to transient-stress analysis (transient thermal and structural) using ANSYS software. A complete evaluation of temperature, heat flux and resulting stress distribution across the vessel was estimated at four different locations within the designed PV and the obtained result was compared with analytically obtained results from appropriate standards. The accuracy of the result obtained from PV was validated using analysis of Mesh Independent Study (MIS), Grid Convergence Index (GCI) and fractional error obtained between the fine grid used. The results showed that there were different temperature and heat flux distribution at the considered locations, these varied distributions or change are according to various transients which are as a result of the load applied to the PV. The simulated maximum principal stress value was close to the analytically computed stress with a percentage error of 2.65% with respect to the analytically obtained result. The analysed maximum stress (W analysed) value 3400 MPa, obtained from MIS study was close to 3210 MPa obtained for maximum stress using numerical approach (WN). The GCI value obtained was 0.073 and fractional error of -0.003 which show that the result presented are grid independent solution.